METHODS OF IMPROVING FOREIGN INVESTMENTS IN THE ECONOMY OF UZBEKISTAN (International Journal of Innovative Technologies in Economy, 2018)
In article ways of development of economy of the Republic of Uzbekistan, improvement of attraction of foreign investments for the organization of the modern cooperation small enterprises making a finished product on the basis of processing of valuable raw materials and ensuring integration into world economy are stated.